The Ranking of Southern Ports and Islands of Iran for Seawater Desalination Plants Using ELECTRE III Method - Ali Mostafaeipour; Mohammad Saidi-Mehrabad; Mostafa Rezaei; Mojtaba Qolipour (Journal of Renewable Energy and Environment, 2017)
The energy insecurity, environmental pollution, climate change and even reduced rainfall in some countries are prime examples of consequences of the world’s excessive reliance on fossil fuels. This study suggests that in some southern islands and coastal areas of Iran, two such problems, namely the growing shortage of potable water and air pollution can be addressed by building a wind-powered seawater desalination plant at the locations. To evaluate such project, first the sites that may provide the highest efficiency need to be identified. In this study, 10 ports and 5 islands in southern Iran, which suffer from water shortage but have access to seawater, are identified as preliminary candidate sites for such project. The criteria influencing the suitability of a location are considered to be wind power density, economic feasibility, topographic condition, frequency of natural disasters, population, and the wind farm’s distance from desalination facility. After analyzing and weighting the criteria, the locations are ranked using the ELECTRE III method, and the results are validated using the PROMETHEE method. In conclusion, the results of ranking techniques show that Qeshm Island is the best location for construction of a wind-powered seawater desalination plant.